2022
DOI: 10.1021/acs.inorgchem.2c02467
|View full text |Cite
|
Sign up to set email alerts
|

Deep Blue Phosphorescence from Platinum Complexes Featuring Cyclometalated N-Pyridyl Carbazole Ligands with Monocarborane Clusters (CB11H12)

Abstract: The utilization of deep blue phosphorescent materials in high-performance displays and solid-state lighting requires high quantum efficiencies and color purities. Here, we describe the preparation and luminescent properties of novel platinum triplet emitters featuring cyclometalated N-pyridyl-carbazole ligands functionalized with closo-monocarborane clusters [CB 11 H 12 ] − . All reported complexes were fully characterized by using standard small molecule techniques (UV−vis, cyclic voltammetry, nuclear magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…In another project, the monocarborane clusters combined with the N-pyridyl carbazole ligand improved the bis-NHC Pt(II) complexes' emission quantum yield to 60% at the blue region of 439 nm. 35 Inspired by these results, we concluded that the three-dimensional monocarborane clusters can surely balance the complexes' net charge, and also can improve the triplet emitters' photophysical properties by perturbing the electronic energy levels in the excited states.…”
mentioning
confidence: 74%
“…In another project, the monocarborane clusters combined with the N-pyridyl carbazole ligand improved the bis-NHC Pt(II) complexes' emission quantum yield to 60% at the blue region of 439 nm. 35 Inspired by these results, we concluded that the three-dimensional monocarborane clusters can surely balance the complexes' net charge, and also can improve the triplet emitters' photophysical properties by perturbing the electronic energy levels in the excited states.…”
mentioning
confidence: 74%
“…S4, ESI †) supported the 3 LLCT and 3 MLCT nature of their phosphorescence, which will be discussed in the next paragraph. The radiative rate constants (k r ) and nonradiative rate constants (k nr ) were calculated from the quantum yield and lifetime using the following mathematical equations: 13,27 k r = F PL /t…”
Section: X-ray Crystallography and Thermal Propertiesmentioning
confidence: 99%
“…1). 22 The first type is Pt with four a Key Laboratory of Chemistry and Engineering of Forest Products, State Ethnic monodentate ligands, 23 the second type is Pt with one bidentate ligand and two monodentate ligands, 24,25 the third group is Pt with two bidentate ligands, 26,27 the fourth group is Pt with one tridentate ligand and one monodentate ligand, [28][29][30][31][32][33][34] and the last case is Pt embraced with one tetradentate ligand. 9,35,36 Among these five coordination pattern types, Pt complexes with four monodentate ligands and those bearing one tridentate and one monodentate ligand are often used for chemical probing, 24,[37][38][39] while the remaining three groups are explored for the OLED applications because of their better thermal stability and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,23 Hence, higher overall internal quantum efficiency can be achieved. Meanwhile, Pt(II) normally adopts a square planar coordination geometry, 24 leaving two vacant sites in the perpendicular z-axis. Therefore, it is possible to form intermolecular p-p stacking and Pt-Pt coupling in the solid state.…”
Section: Introductionmentioning
confidence: 99%